The treasure of Ukraine: people’s art as first source of formation of modem Ukrainian design - Koltukova, A.V. (Pedagogy of Higher and Secondary Education, 2006)
The treasure of Ukraine: people’s art as first source of formation of modem Ukrainian the analysis of modem Ukrainian design has shown that its primary’ source was the Ukrainian folk art. The influence of ethnic traditions of work with natural dye-stuff, threads, wax and fabric is quite obvious in the modern tendencies, which are realized in the design of clothes, interior, architectural-landscape compositions and in decorative applied art in general. So, only dye to the reconstruction of old technologies and its harmonious connection with new and interesting ideas and forms can provide the following stage of development of the original and national art.